Herbal Medicine Centre, Techiman - Yeboah, Seth Kwabena (2012)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of Postgraduate Diploma in Architecture